Best Practices in Athletic Donor Relations: The NCAA Football Bowl Subdivision - Liz Wanless; David A. Pierce; J. Michael Martinez; Heather J. Lawrence-Benedict; Nick Kopka (Journal of Applied Sports Management, 2017)
The purpose of this investigation was to identify best practices in intercollegiate athletic donor relations for the National Collegiate Athletic Association (NCAA) Football Bowl Subdivision (FBS). Neither philanthropy research nor athletic fund-raising research presents a contemporary model of donor relations best practices. Additionally, athletic development tactics are given little attention in evidence-based literature. To investigate this topic, three rounds of the Delphi method were completed by 17 intercollegiate athletic development directors in the FBS. Forty-two best practices for donor acquisition and 38 best practices for donor retention and upgrade emerged. Implications for intercollegiate athletic development campaigns are addressed. Subscribe to JASM
Keywords: FBS; athletic development; fundraising; best practices